An NPPB Promoter Polymorphism Associated With Elevated N‐Terminal pro–B‐Type Natriuretic Peptide and Lower Blood Pressure, Hypertension, and Mortality. Issue 4 (April 2017) - Seidelmann, Sara B.; Vardeny, Orly; Claggett, Brian; Yu, Bing; Shah, Amil M.; Ballantyne, Christie M.; Selvin, Elizabeth; MacRae, Calum A.; Boerwinkle, Eric; Solomon, Scott D.
Abstract : Background: Elevated B‐type natriuretic peptide (BNP) levels are associated with heart failure and increased mortality in the general population. We investigated rs198389, a functional variant in the promoter region of the BNP gene ( NPPB ), in patients from the Atherosclerosis Risk in Communities Study to investigate associations with N‐terminal pro‐BNP (NT‐proBNP) levels and outcomes. Methods and Results: A total of 11 361 black and white patients with rs198389 genotyping attended visit 1 (aged 45–64 years; 1987–1989), with follow‐up visits occurring every 3 years (visit 2–visit 4, 1990–1999), followed by visit 5 (2011–2013). NT‐proBNP levels were measured at visits 2, 4, and 5. At visit 2, the GG genotype (frequency 18%) was associated with a 41% higher mean plasma level of NT‐proBNP compared with the AA genotype (frequency 34%), with intermediate values observed in AGs ( P =4.2×10 −52 ). The GG genotype was associated with reduced systolic blood pressure (−1.6 mm Hg, P =0.006), diastolic blood pressure (−1 mm Hg, P =0.003), antihypertension medication use (odds ratio, 0.85; 95% CI, 0.74–0.97 [ P =0.02]), and hypertension (odds ratio, 0.81; 95% CI, 0.72–0.92 [ P =0.002]) compared with the AA genotype with intermediate values in AGs. These relationships persisted throughout subsequent visits. After a median follow‐up of 23 years, there were 4031 deaths. With and without covariate adjustment, the GG genotype was associated with modestly lower mortality (hazard ratio, 0.86; 95% CI, 0.78–0.95), primarily reflective of cardiovascular death (hazard ratio, 0.75; 95% CI, 0.61–0.92), and increased residual lifespan of 8 months from 50 years of age ( P =0.02) versus AAs. Conclusions: The rs198389 G allele in the NPPB promoter is associated with elevated levels of NT‐proBNP throughout adult life, reduced blood pressure, hypertension and cardiovascular mortality, and increased lifespan.